Formal Semantics, Lexical Semantics, and Compositionality: The Puzzle of Privative Adjectives (Philologia, 2021)
The focus of the paper is the interaction of meaning and context with different kinds of adjectives. Adjective meanings are shown to be more constrained than was appreciated in earlier work. Facts about “NP-splitting” in Polish and Russian cast serious doubt on the standard hierarchy of adjectives, and the data become much more orderly if privative adjectives are reanalyzed as subsective adjectives. This revised account requires the possibility of coerced expansion of the denotation of the noun to which an adjective is applied. Compositionality can be seen as one of the driving forces in such context-sensitive meaning shifts.
Keywords: Formal semantics; compositionality; coercion; context-dependence; adjectives; privative; subsective; Polish; Russian; NP-splits